the answer to this question would be 0.185185185185185
For this case what you should do is evaluate values of x in the function and verify that they meet the result of f (x) shown in the graph.
The answer is
f (x) = - 2lxl +1
notice that
f (1) = - 2l1l + 1 = -1
f (-1) = - 2l-1l + 1 = -1
Both comply with the value of f (x) shown in the graph
answer
f (x) = - 2lxl +1
Answer:
It will leave the sprinkler at speed of ![v_2=613.87m/sec](https://tex.z-dn.net/?f=v_2%3D613.87m%2Fsec)
Step-by-step explanation:
We have given internal diameter of the garden hose ![d_1=0.740in=1.8796cm](https://tex.z-dn.net/?f=d_1%3D0.740in%3D1.8796cm)
So radius ![r_1=\frac{d_1}{2}=\frac{1.8796}{2}=0.9398cm](https://tex.z-dn.net/?f=r_1%3D%5Cfrac%7Bd_1%7D%7B2%7D%3D%5Cfrac%7B1.8796%7D%7B2%7D%3D0.9398cm)
So area ![A_1=\pi r_1^2=3.14\times 0.9398^2=2.7733cm^2](https://tex.z-dn.net/?f=A_1%3D%5Cpi%20r_1%5E2%3D3.14%5Ctimes%200.9398%5E2%3D2.7733cm%5E2)
Water in the hose has a speed of 4 ft/sec
So ![v_1=4ft/sec=121.92cm/sec(As\ 1ft/sec\ =30.48cm/sec)](https://tex.z-dn.net/?f=v_1%3D4ft%2Fsec%3D121.92cm%2Fsec%28As%5C%201ft%2Fsec%5C%20%3D30.48cm%2Fsec%29)
Number of holes n = 36
Diameter of each hole ![d_2=0.1397cm](https://tex.z-dn.net/?f=d_2%3D0.1397cm)
So radius ![r_2=0.0698cm](https://tex.z-dn.net/?f=r_2%3D0.0698cm)
So area ![A_2=\pi r^2=3.14\times 0.0698^2=0.0153cm^2](https://tex.z-dn.net/?f=A_2%3D%5Cpi%20r%5E2%3D3.14%5Ctimes%200.0698%5E2%3D0.0153cm%5E2)
From continuity equation
![A_1v_1=nA_2v_2](https://tex.z-dn.net/?f=A_1v_1%3DnA_2v_2)
![2.7733\times 121.92=36\times 0.0153\times v_2](https://tex.z-dn.net/?f=2.7733%5Ctimes%20121.92%3D36%5Ctimes%200.0153%5Ctimes%20v_2)
![v_2=613.87m/sec](https://tex.z-dn.net/?f=v_2%3D613.87m%2Fsec)
Answer:
0
Step-by-step explanation:
m=(y2-y1)/(x2-x1)
m=(7-7)/(5-(-1))
m=0/(5+1)
m=0/6
m=0
Answer:
y = 3x-6
Step-by-step explanation:
y = 3x−5
This is in slope intercept form
y = mx+b where m is the slope and b is the y intercept
m =3
Parallel lines have the same slope
We have the slope m=3 and a point (2,0)
y = mx+b
y = 3x+b
Substituting the point into the equation to solve for b
0 = 3(2)+b
0 = 6+b
b = -6
y = 3x-6